Research trends in isolation and identification of bacteria from Indonesia with various roles: Review Article - Nuryady, Moh. Mirza; Aisha, Aisha; Aulia, Diva; Savitri, Aulia (Journal of Biotechnology and Natural Science, 2021)
Bacteria are agents that can be used widely and are genetically easy to manipulate and reproduce. Many studies related to the isolation and identification of bacterial isolates from Indonesia have been carried out for various purposes. This research is still ongoing and has never been informed about the abundance of data from previous studies. The purpose of this study is to provide an overview of research topic trends related to the isolation and identification of bacterial isolates from Indonesia. The method used in this review is by setting inclusion and exclusion criteria and selecting a random sample of articles for analysis. The results of a review of research trends in isolation and identification of bacterial isolates from Indonesia showed four main topics discussed, namely the topics of food processing, agriculture, health, and bioremediation. Analysis of 41 articles shows that the most common discussion is the exploration of Lactate Origin-producing bacteria, the role of improving food quality. Furthermore, it was identified that the most isolated bacterial isolates came from food and plants, with 14 publications from a total of 41 articles. It can be concluded that exploratory research on Lactic Acid Bacteria for improving the quality of food products is currently the most studied topic by researchers in Indonesia.